Gouverner l’agriculture grâce aux modèles ? Le cas du CAADP au Mozambique - Nelly Leblond (Unité Mixte de Recherche 8504 Géographie-cités, 2017)
The agricultural policies aligned on the Comprehensive Africa Agriculture Development Programme (CAADP) are coproduced with economic models. Models became hegemonic in a context of foreign aid dependency and of elite’s socialization through economic modelling. Based on grey literature and observations in Mozambique, we analyze the contribution of modeling to this policy making. While officially promoting the objectives of ownership, efficiency, and evidence-based policies, modeling enables the coexistence of contradicting claims and acts. CAADP and models are an apparatus instrumentalized by political and agro-industrial elites. Their coproduction therefore enables the reproduction of economic and political strategies it claimed to suppress. Our results call for a reappraisal of the multiple appropriations of modeling and of the effects of the agricultural policies promoted.